Implementasi Sistem Monitoring Jaringan Kantor PT Mitra Solusi Infokom Menggunakan Manageengine Opmanager dengan Metode SNMP Protocol - Irvan Irvan; Perani Rosyani (Journal of Information System Research (JOSH), 2021)
PT Mitra Solusi Infokom (MSInfokom) is an IT System Integrator company engaged in Technology and Communication Infrastructure. Network monitoring in MSInfokom is still done manually and still relies on conventional methods, so it has an impact on the efficiency of the time used by the Network Operation Center (NOC) because it has to do direct tracking on existing devices. This thesis aims to design and build a network monitoring system using ManageEngine OpManager with the SNMP Protocol method. The result obtained from the use of this network monitoring application is to monitor the device in real time, where the system will send notifications via email in case of a malfunction or downtime on the existing device.